Spectroscopy and Structural Investigation of Iron Phosphorus Trisulfide—FePS3. Issue 7 (12th February 2022) - Budniak, Adam K.; Zelewski, Szymon J.; Birowska, Magdalena; Woźniak, Tomasz; Bendikov, Tatyana; Kauffmann, Yaron; Amouyal, Yaron; Kudrawiec, Robert; Lifshitz, Efrat
Abstract: Lamellar structures of transition metal phosphorus trisulfides possess strong intralayer bonding, albeit adjacent layers are held by weak van der Waals interactions. Those compounds received enormous interest due to their unique combination of optical and long‐range magnetic properties. Among them, iron phosphorus trisulfide (FePS3 ) gathered special attention for being a semiconductor with an absorption edge in the near‐infrared, as well as showing an Ising‐like anti‐ferromagnetism. A successful growth of centimeter size bulk FePS3 crystals with a chemical yield above 70% is reported, whose crystallographic structure and composition are carefully identified by advanced electron microscopy methodologies, including atomic resolution elemental mapping, along with photoelectron spectroscopy. The knowledge on the optical activity of FePS3 is extended utilizing temperature‐dependent absorption and photoacoustic spectroscopies, while measurements are corroborated with density‐functional theory calculations. Temperature‐dependent experiments show a small and monotonic band‐edge energy shift down to 115 K and expose the interconnected importance of electron‐phonon coupling. Most of all, the correlation between the optical behavior and the magnetic phase transition is revealed, which shows the practical utilization of temperature‐dependent optical absorption to investigate magnetic interactions. Abstract : Iron phosphorus trisulfide (FePS3 ) receives great attention as a layered semiconductor with a bandgap in the infrared region, simultaneously exhibiting antiferromagnetism at cryogenic temperatures. Using photoacoustic and absorption experiments, optical transitions and their temperature evolution are identified, revealing the influence of the magnetic phase transition on optical properties of FePS3 and electron‐phonon coupling strength, relevant for magneto‐optic and light detection applications.